Change in Stress Among Individuals with Chronic Health Conditions and Low Health Literacy Using a Tailored Communication App Promoting Self-Management - Raymond L. Ownby; Joshua Caballero (Behavioral Sciences)
Chronic disease self-management (CDSM) is critical for improving health outcomes, particularly for individuals with low health literacy who face barriers in accessing and understanding medical information. This study examined the role of tailored digital health interventions in reducing stress and improving quality of life among individuals with chronic conditions. A multisite randomized controlled trial including 309 participants at baseline aged 40 to 90 years was conducted using a mobile app that provided self-management information at different literacy levels. Latent growth curve modeling (LGM) computed in Mplus was used to assess changes in stress over time and its impact on quality of life. The results indicated that successful tailoring of health information was significantly associated with reductions in perceived stress, which, in turn, predicted improvements in quality of life. These findings suggest that personalized digital interventions may enhance engagement with self-management strategies, alleviate psychological distress, and contribute to better overall well-being. This study highlights the importance of tailoring health content to users’ literacy levels and informational needs, underscoring the potential of mobile health solutions for improving CDSM. Future research should explore additional mechanisms underlying these effects and assess the long-term sustainability of digital interventions in diverse populations. These results provide valuable insights into optimizing mobile health applications to support individuals with chronic conditions.